Cerebral palsy: current status of the problem (review of literature) - E. V. Kolesnikova; I. A. Vyshlova; S. M. Karpov; O. A. Soboleva (Русский журнал детской неврологии)
The article presents an overview of current literature data on the description of risk factors, epidemiology, etiology, clinical presentation, diagnosis, prevention and treatment of cerebral palsy (CP).Cerebral palsy is the most common pathology that leads to disability in childhood, with impaired motor function as a result of damage to the central nervous system. With CP, there is a wide range of disorders that disrupt the daily activities of the child. In addition, cognitive and behavioral problems, communication disorders, and the appearance of epileptic seizures are possible. Previously it was believed that the cause of CP is a lack of oxygen at birth. However, modern research has established that, along with this, there are many other causes and risk factors that together cause brain damage during ontogenesis and contribute to the development of the pathological process. This literature review aims to highlight current developments in the field of CP and identify new avenues for future research in this area.